Dynamic accumulators-based authenticated group key management scheme for heterogeneous wireless sensor network - Xiao-rui ZHONG; Chun-guang MA (Tongxin xuebao)
Witnesses of a dynamic accumulator (DA) can ensure whether an object has been accumulated.On the basis of this,node membership in a cluster was verified and a novel authenticated group key management protocol was proposed,which supports node revocation and addition.In order to establish a group key for a cluster,each member provides their assigned number to join accumulation.DAAG can not only guarantee the confidentiality of witnesses,but also keep non-members from calculating novel group keys by binding witness with group key update.The security and performance analyses show that DAAG is resistant against replay attack,forgery attack and collusion attack,and can provide forward security and backward security.